2016
DOI: 10.5606/archrheumatol.2016.5739
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Impairment and Subclinical Atherosclerosis in Rheumatoid Arthritis Patients Without Traditional Cardiovascular Risk Factors

Abstract: Objectives: This study aims to evaluate the association of hearing impairment with carotid intima-media thickness and subclinical atherosclerosis in rheumatoid arthritis (RA) patients. Patients and methods: A total of 41 RA patients (2 males, 39 females; mean age 46.5±10.2 years; range 20 to 63 years) with no known traditional cardiovascular risk factors were included. Routine clinical and laboratory assessments for RA patients were performed. Pure tone air (250-8000 Hz) and bone conduction (250-6000 Hz) thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 26 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…There was disagreement in the literature regarding the association between the use of chloroquine/hydroxychloroquine and hearing loss. Most studies reported the lack of association between the use of hydroxychloroquine/chloroquine and hearing loss [15,19,22,24,25]. Roverano, et al [15] reported that 16 patients using hydroxychloroquine (200 mg/day) had sensorineural hearing loss, but when comparing groups, there was no correlation between the presence of hearing loss and treatment with this drug.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…There was disagreement in the literature regarding the association between the use of chloroquine/hydroxychloroquine and hearing loss. Most studies reported the lack of association between the use of hydroxychloroquine/chloroquine and hearing loss [15,19,22,24,25]. Roverano, et al [15] reported that 16 patients using hydroxychloroquine (200 mg/day) had sensorineural hearing loss, but when comparing groups, there was no correlation between the presence of hearing loss and treatment with this drug.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Seven studies analyzed the use of chloroquine and/or hydroxychloroquine in participants with SLE [15][16][17][18][19][20][21], 6 in participants with rheumatoid arthritis [20,[22][23][24][25][26], 2 in participants with malaria [3,27], 2 without definition of the disease treated [28,29], and 1 in healthy participants [30].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In rheumatoid arthritis, subclinical atherosclerosis pathology was associated with hearing impairment in a group of 41 patients. 36 Methotrexate in RA improved inflammation and audiograms 1 just as statin use improved hearing acuity 27,28 and lessens inflammation 37 in the general population. These results suggest that audiometry can be used to track improvement and deterioration of both hearing and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%